Uniaxial tensile material properties of adult Chinese dura mater: investigating the influence of age, sex, and anatomical site - Wang, Jinming; Cai, Changsheng; Wan, Lei; Liu, Ao; Deng, Kaifei; Fan, Ying; Zhang, Jianhua; Huang, Jiang; Wan, Changwu; Zou, Donghua; Li, Zhengdong (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study investigated the biomechanical properties of the dura mater from 29 Chinese adult donors (20 -86 years), focused on the influence of age, anatomical region, sex and loading direction, to establish Chinese population - specific material parameters for cranial finite element (FE) models and enhance forensic traumatic brain injury analysis.MethodsIn this study, a total of 275 dural specimens were prepared and categorized into young adult (20-44 years), middle aged (45-64 years), and elderly (≥65 years) cohorts. Samples were excised from frontal, temporal, parietal and occipital regions and tested uniaxially in sagittal and coronal directions, with strain measured via digital image correlation (DIC) techniques. True stress-strain curves were fitted to the Raghavan model to determine elastic fiber modulus (EE), collagen fiber modulus (EC), failure stress (σTf), and failure strain (εTf); ultimate tensile force (MaxForce) was also recorded. Histological analysis assessed age-related microstructural changes.Resultsindicated significant age-related degradation: EC, σTf, εTf; and MaxForce significantly decreased with age (median EC declined from 28.0 MPa in young adults to 15.3 MPa in the elderly, P < 0.05; median εTf from 0.215 to 0.156, P < 0.05), while EE showed no significant age correlation (P = 0.10). Significant regional variance were observed, with the parietal region exhibiting higher EE (P = 0.01) and σTf (P = 0.03) compared to the occipital region; εTf showed no significant regional differences (P = 0.12). Dura mater demonstrated clear anisotropy: sagittal loading yielded significantly higher median EC (27.0 MPa vs. 18.1 MPa coronal, P = 0.003), σTf (4.30 MPa vs. 3.18 MPa coronal, P = 0.020), and MaxForce (12.9 N vs. 10.3 N coronal, P = 0.014). No statistically significant sex-based differences were found for any parameter (P > 0.05). Histology confirmed progressive age-related collagen disorganization and elastic fiber degradation. In conclusion, Chinese adult dura mater exhibits significant age-dependent decline in mechanical integrity, clear anisotropy favoring the sagittal direction, and notable regional heterogeneity, but no significant sex-based differences.ConclusionThese findings provide crucial, population-specific data for improving the biofidelity of FE head models and forensic injury analysis.